The development of chemistry at the National Medical Institute, 1888-1915 - Schifter, Liliana; Aceves Pastrana, Patricia (Circumscribere International Journal for the History of Science, 2015)
In the present paper we analyze the contributions of the National Medical Institute (NMI) to the development of chemistry in Mexico at the end of the 19th century and beginning of the 20th century mainly through the work carried out in two of its sections: Analytical chemistry and Department of Industrial Chemistry. NMI had the most modern laboratories of the time for the advancement of analytical chemistry, where leading scientists carried out research with the common goal of investigating the therapeutic effects of national medicinal plants. The Department of Industrial Chemistry began its activities in 1904 with the aim of perfecting the process for large-scale production of drugs and active ingredients obtained at NMI laboratories. This was undoubtedly the first research facility in which specialists in the field put the main methods of industrial pharmaceutical chemistry into practice. The Department was created with the double goal of obtaining raw materials and medicines useful for the public in general and to contribute to the training of skilled manpower.